The Impact of Parent's Upbringing on the Social Identity of the Adolescents Used Vape in Pekanbaru - Sagita, Adela; Armayanti, Leni (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
Social identity is the conception of an individual's identity as part of his group compared with others. The purpose of this study was to determine the effect of parenting style on social identity in young women who use vape in Pekanbaru. The subjects of this study were 139 people; the exact population is not known, and the criteria of young women who use vape aged 15-23 years. The sampling technique used is Snowball Sampling. This data was analyzed using Partial Least Square (PLS) with smartPLS3.0 M3 software. The results of this study indicate that parenting style has a positive and significant effect on social identity, with a path coefficient value of 0.334, a value of 0.006<0.05, and a value of 2.781. It means that the higher the parenting style, the higher the social identity of young women who use vape in Pekanbaru.